The effects of a self‐observation‐based meditation intervention on acceptance or rejection of the other. (1st October 2015) - Pinazo, Daniel; Breso, Edgar
Abstract : Research has demonstrated the many benefits of mindfulness training programmes for individual health and well‐being. This study, however, explored whether mindfulness training might have effects on intergroup interaction. We tested the effects of a self‐observation‐based mindfulness course on several dimensions of acceptance of the other (i.e., non‐judgement, non‐reaction and observation). An initial study test a mindfulness course training ( N  = 197). A second study then tested its effect on intergroup relationships ( N  = 120). A control group was used in both studies, and the subjects were tested before and after the course. Results indicate that participation in the course favoured intergroup acceptance of the other and suggest that mindfulness training represents a useful educational method for reducing social discrimination.